(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
The article analyzes the pedagogical and scientific significance of implementing the credit-module system in medical education. The credit-module system provides students with opportunities for independent learning, increases the transparency of the educational process, and facilitates the integration of theoretical knowledge with practical skills. The competency-based approach focuses on developing students’ professional knowledge and skills and is one of the key components of modern medical education. The article substantiates the compatibility of the credit-module system with competency-based education, their advantages, and their role in medical education.